Field Localization and Density Cavitation in Low-Beta Plasmas. (28th November 2021) - Rinawa, Motilal; Chauhan, Prashant; Kumar, Sintu; Singh, Manoj Kumar; Singh, Hari Kumar; Sharma, Amit; Sharma, R. P.
Abstract : In the present paper, filamentous structure formation, associated turbulent spectrum, and density cavity formation phenomena have been investigated for low-β plasma β ≪ m e / m i applicable to the auroral region. A set of dimensionless equations governing the dynamics of three dimensionally propagating inertial Alfvén wave (3D-IAW) and perpendicularly propagating magnetosonic wave (PMSW) has been developed. Ponderomotive force due to 3D-IAW has been included in the dynamics of the PMSW. Numerical simulation has been performed to study the nonlinear coupling of these two waves. From the obtained results, we found that the field intensity localization takes place which may further lead to the additional dissipation/turbulence process for particle heating and acceleration in space plasma. The associated turbulent spectrum is obtained with scaling nearly k − 4.28 at smaller scales (in the dissipation range). Relevance of the obtained results with the observations reported by various spacecrafts such as Hawkeye and Heos 2 has been discussed. Also, density fluctuations (depletion) of ∼ 0.10 n 0 are calculated, which are consistent with the FAST spacecraft observation reported.